Application of Verticulture Techniques in Learning to Increase Environmental Awareness and Interest in Agriculture among Children in Kemiri Village, Puspo District, Pasuruan - Nurussyahban, Al Hisyam; Aldila, Fitri Yulinar; Permana Putra, Mas Ardian; Rozci, Fatchur (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
This program aims to foster environmental awareness and interest in farming in children in Kemiri Village, Pasuruan Regency. Through educational approach and hands-on practice, the children were taught about verticulture technique, which is vertical plant cultivation. This activity includes counseling on the basic concepts of verticulture, planting training, and assistance in plant care. The results showed an increase in children's understanding of the importance of sustainable agriculture and basic skills in farming. By using simple and easily available planting media, this program successfully facilitates fun and effective learning. It is hoped that this program can inspire children to implement verticulture practices in the surrounding environment and become a generation that cares about the environment.